Indian Bt Cotton Varieties Do Not Affect the Performance of Cotton Aphids - Lawo, Nora C. (Public Library of Science, 2009)
Cotton varieties expressing Cry proteins derived from the soil bacterium Bacillus thuringiensis (Bt) are grown worldwide for the management of pest Lepidoptera. To prevent non-target pest outbreaks and to retain the biological control function provided by predators and parasitoids, the potential risk that Bt crops may pose to non-target arthropods is addressed prior to their commercialization. Aphids play an important role in agricultural systems since they serve as prey or host to a number of predators and parasitoids and their honeydew is an important energy source for several arthropods. To explore possible indirect effects of Bt crops we here examined the impact of Bt cotton on aphids and their honeydew. In climate chambers we assessed the performance of cotton aphids, Aphis gossypii Glover (Hemiptera: Aphididae) when grown on three Indian Bt (Cry1Ac) cotton varieties (MECH 12, MECH 162, MECH 184) and their non-transformed near isolines. Furthermore, we examined whether aphids pick up the Bt protein and analyzed the sugar composition of aphid honeydew to evaluate its suitability for honeydew-feeders. Plant transformation did not have any influence on aphid performance. However, some variation was observed among the three cotton varieties which might partly be explained by the variation in trichome density. None of the aphid samples contained Bt protein. As a consequence, natural enemies that feed on aphids are not exposed to the Cry protein. A significant difference in the sugar composition of aphid honeydew was detected among cotton varieties as well as between transformed and non-transformed plants. However, it is questionable if this variation is of ecological relevance, especially as honeydew is not the only sugar source parasitoids feed on in cotton fields. Our study allows the conclusion that Bt cotton poses a negligible risk for aphid antagonists and that aphids should remain under natural control in Bt cotton fields.